2009
DOI: 10.1039/b817093b
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of complexed block copolymers

Abstract: Due to their ability to microphase separate into well ordered structures with periodicities on the nanometre scale, block copolymers have received widespread attention as building blocks for the fabrication of nanomaterials. In particular, thin films of block copolymers promise new technological breakthroughs in e.g. computer memory applications. This Review gives a short overview of progress that has been made in preparing suitable thin films of conventional coil-coil diblock copolymer systems, while the adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
86
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 190 publications
(235 reference statements)
1
86
0
Order By: Relevance
“…Their morphology can be controlled by changing the block composition and interaction strength, while the characteristic size of the self-assembled structures can be adjusted by varying the molecular weight of the constituent polymers. Indeed, block copolymers can be used to generate well-controlled, periodic patterns that can be used as templates or scaffolds in various applications ranging from microelectronics to biosensors [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Their morphology can be controlled by changing the block composition and interaction strength, while the characteristic size of the self-assembled structures can be adjusted by varying the molecular weight of the constituent polymers. Indeed, block copolymers can be used to generate well-controlled, periodic patterns that can be used as templates or scaffolds in various applications ranging from microelectronics to biosensors [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the self-assembly of polymers, especially block copolymers, has aroused an increasing research interest [15,16] due to their abundant self-assembly behaviors. The micellization and microphase separation of block copolymers in solutions and thin films have been utilized extensively to fabricate the organized composite structures of polymer/nanoparticles [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] By templating the self-assembly of small molecules, surfactant, and block copolymers, nanoporous structures with different sizes can be prepared. [12][13][14] The porous structure generated by template removal has pore sizes in the range of 10 nm to 1 ÎŒ m. Wiesner and co-workers [ 15 ] reported that the self-assembly of a block copolymer and ligand-stabilized platinum NPs at a high NP loading produced an ordered mesoporous platinum-carbon nanocomposite with open and large pores ( > 10 nm) after the pyrolysis of the inverse hexagonal hybrid mesostrucuture.…”
Section: Introductionmentioning
confidence: 99%